2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20471
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Entrepreneurial Characteristics and Experiences of Engineering Alumni

Abstract: Her research interests focus on educational studies that can help improve teaching, learning, and educational policy decision makings using both quantitative and qualitative research methods. Her current research project in National Center for Engineering Pathways to Innovation (Epicenter) focuses on measuring engineering students' entrepreneurial interests and related individual characteristics. Her Ph.D. dissertation involved using statistical modeling methods to explain and predict engineering students' suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The development of entrepreneurship based centers and clubs have also played a key role in developing EM in engineering undergraduates through making connections between the classroom and the real world, building a sense of community, and providing a space for EM activities outside the classroom (Ndou et al., 2018; Ridley, 2016). Partaking in these types of clubs and activities have been shown to increase entrepreneurial interest in students, with many more graduates leaning towards starting their own businesses in the future (Rodriguez et al., 2018). Although not as heavily studied, undergraduate research has also been shown to have a positive impact on students' EM in terms of confidence, social skills, emotional intelligence, and critical thinking (Yasuhara et al., 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of entrepreneurship based centers and clubs have also played a key role in developing EM in engineering undergraduates through making connections between the classroom and the real world, building a sense of community, and providing a space for EM activities outside the classroom (Ndou et al., 2018; Ridley, 2016). Partaking in these types of clubs and activities have been shown to increase entrepreneurial interest in students, with many more graduates leaning towards starting their own businesses in the future (Rodriguez et al., 2018). Although not as heavily studied, undergraduate research has also been shown to have a positive impact on students' EM in terms of confidence, social skills, emotional intelligence, and critical thinking (Yasuhara et al., 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The push for undergraduate engineering students to develop an Entrepreneurial Mindset (EM) is becoming more widely encouraged as research continues to support that students with an EM are in high demand within industrial positions [1][2][3][4][5][6]. Possessing an EM is often associated with characteristics such as motivation, understanding of business processes, communication, innovation, and creativity [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%